Makna Simbolik Kultus Kargo dalam Cerita Rakyat Gresi Selatan: Asal Mula Terjadinya Kali Khubu: The Symbolic Meaning of the Cargo Cult in South Gresi Folktale: The Origin of the Khubu River - Siswanto Siswanto (Balai Bahasa Provinsi Papua, 2021)
This study was intended to describe the symbolic meaning of cargo cult in Gresi folklore through semiotic theory. To analyze the symbolic meaning of cargo cult in Gresi folklore, interpretive descriptive method is used by utilizing interpretive methods and presenting them in a descriptions. Data was collected using interview and note-taking techniques, then analyzed using semiotic content analysis. Analysis shows that the symbolic meaning of cargo cult in Gresi folklore is clearly reflected. The results of this study indicate that cargo movement is not just an economic event caused by a life that is economically deprived, which then arouses the longing for the presence of a new world of abundance. The cargo movement of the Gresi people is also a cultural attitude and an attitude of religious life that can provide spiritual powers that will bring renewal in their lives.